Donor sex, age and ethnicity impact stored red blood cell antioxidant metabolism through mechanisms in part explained by glucose 6-phosphate dehydrogenase levels and activity - D'Alessandro, Angelo; Fu, Xiaoyun; Kanias, Tamir; Reisz, Julie A; Culp-Hill, Rachel; Guo, Yuelong; Gladwin, Mark T; Page, Grier; Kleinman, Steven; Lanteri, Marion; Stone, Mars; Busch, Michael P; et al. (Haematologica (Roma), 2021)
Red blood cell storage in the blood bank promotes the progressive accumulation of metabolic alterations that may ultimately impact the erythrocyte capacity to cope with oxidant stressors. However, the metabolic underpinnings of the capacity of RBCs to resist oxidant stress and the potential impact of donor biology on this phenotype are not known. Within the framework of the REDS-III RBC-Omics study, RBCs from 8,502 healthy blood donors were stored for 42 days and tested for their propensity to hemolyze following oxidant stress. A subset of extreme hemolyzers donated a second unit of blood, which was stored for 10, 23, and 42 days and profiled again for oxidative hemolysis and metabolomics (599 samples). Alterations of RBC energy and redox homeostasis were noted in donors with high oxidative hemolysis. RBCs from females, donors over 60 years old, donors of Asian/South Asian race-ethnicity, and RBCs stored in additive solution-3 were each independently characterized by improved antioxidant metabolism compared to, respectively, males, donors under 30 years old, Hispanic and African American race ethnicity donors, and RBCs stored in additive solution-1. Merging metabolomics data with results from an independent GWAS study on the same cohort, we identified metabolic markers of hemolysis and G6PD-deficiency, which were associated with extremes in oxidative hemolysis and dysregulation in NADPH and glutathione-dependent detoxification pathways of oxidized lipids. Donor sex, age, ethnicity, additive solution and G6PD status impact the metabolism of the stored erythrocyte and its susceptibility to hemolysis following oxidative insults.